Prediction of shear viscosity of a zinc oxide suspension with colloidal aggregation - Kim, Danbi; Koo, Sangkyun (Korea-Australia rheology journal, 2018)
We deal with scaling relations based on fractal theory and rheological properties of a colloidal suspension to determine a structure parameter of colloidal aggregates and thereby predict shear viscosity of the colloidal suspension using an effective-medium model. The parameter denoted by β is m (3- d f ), where m indicates shear rate ( D ) dependence of aggregate size R , i.e. R ∝ D − m , and d f is the fractal dimension for the aggregate. A scaling relation between yield stress and particle volume fraction φ is applied to a set of experimental data for colloidal suspensions consisting of 0.13 μm zinc oxide and hydroxyethyl acrylate at φ = 0.01-0.055 to determine β . Another scaling relation between intrinsic viscosity and shear rate is used at lower φ than the relation for the yield stress. It is found that the estimations of β from the two relations are in a good agreement. The parameter β is utilized in establishing rheological models to predict shear viscosity of aggregated suspension as a function of φ and D . An effective-medium (EM) model is employed to take hydrodynamic interaction between aggregates into account. Particle concentration dependence of the suspension viscosity which is given in terms of volume fraction of aggregates φ a instead of φ is incorporated to the EM model. It is found that the EM model combined with Quemada’s equation is quite successful in predicting shear viscosity of aggregated suspension.